Optimal Tuning and Placement of Power System Stabilizers Based Eigenvalue - Lawrence Bibaya; Chongru Liu (Institute of Advanced Engineering and Science, 2016)
In this paper, an eigenvalue assignment based Particle Swarm Optimization and Participation Factor for Optimal tuning and placement of power system stabilizers is proposed. The proposed approach presents a two-step methodology to find optimal location and parameters of PSS. The Participation Factor method is computed using the modal analysis toolbox from DIgSILENT, and used to determine the power system stabilizers optimal location. A Particle Swarm Optimization algorithm is written in MATLAB to search the power system stabilizers optimal parameters. Two eigenvalue-based objective functions to ensure a maximum damping of the inter-area modes as well as of the local modes by assigning them in a robust stability area are considered. The performance of the proposed approach is tested and examined on the four-machine two-area power system. Linear modal analysis and non-linear time domain simulations show the robustness of the proposed approach.